2003
DOI: 10.2134/agronj2003.0380
|View full text |Cite
|
Sign up to set email alerts
|

Peanut Response to Cultivar Selection, Digging Date, and Tillage Intensity

Abstract: reduced tillage systems often do not exceed those of conventional tillage. Determining the cause of inconsis-Peanut (Arachis hypogaea L.) in the United States is generally tent yield response to reduced tillage would be benefigrown in conventionally tilled systems. However, interest in reduced tillage peanut production has increased. Five experiments were con-cial in determining when reduced tillage systems could ducted in North Carolina to determine if cultivar selection and digging be successfully implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 3 publications
(6 reference statements)
1
18
0
1
Order By: Relevance
“…The only difference that was observed was in the ST treatment in 2005 when Southern blight had a lower incidence compare to CT. Also, there were trends for reduced levels of Sclerotinia blight for the NT treatment compared to CT and ST treatments. This is supported by Jordan et al (2003), who found reduced tillage decreased sclerotinia blight when considerable residue was left for ground cover prior to planting in North Carolina. However, these authors also noted a great deal of variability across peanut plots due to the residue and disease pressure.…”
Section: Insect Populationsmentioning
confidence: 65%
See 1 more Smart Citation
“…The only difference that was observed was in the ST treatment in 2005 when Southern blight had a lower incidence compare to CT. Also, there were trends for reduced levels of Sclerotinia blight for the NT treatment compared to CT and ST treatments. This is supported by Jordan et al (2003), who found reduced tillage decreased sclerotinia blight when considerable residue was left for ground cover prior to planting in North Carolina. However, these authors also noted a great deal of variability across peanut plots due to the residue and disease pressure.…”
Section: Insect Populationsmentioning
confidence: 65%
“…They observed a delay in leaf spot development with reduced tillage. In North Carolina, reduced tillage decreased sclerotinia blight where considerable residue was left for ground cover prior to planting (Jordan et al, 2003). Grichar and Boswell (1987) observed that no-till systems decreased peanut yield 600 to 2400 kg ha 21 in Texas and cited a lack of weed control and compaction as the reasons for reduced yield.…”
mentioning
confidence: 99%
“…In North Carolina, peanut plantings in reduced tillage increased from 10% to 23% from 1998 to 2004 (6). Yield of peanut planted in reduced tillage systems on finer-textured soils is often lower than yield in conventional tillage systems (6,7). Lower yield of peanut strip tilled into stubble from the previous crop compared with conventional tillage or beds prepared the previous fall can be associated with greater pod loss in the digging process (4).…”
Section: Introductionmentioning
confidence: 99%
“…Peanut growers are interested in adopting some form of reduced tillage production. Research has shown considerable variation in peanut response to tillage (3,5,6,7,16,18). Concern over pod loss and lower yield when peanut is strip tilled can be partially overcome by performing some tillage, in particular establishing beds prior to planting (7).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, five studies have given conservation tillage a clear advantage in either yield, improved quality, or net economic returns (Brandenburg et al 1998;Hartzog and Adams, 1989;Hurt et al, 2006;Marois and Wright, 2003;Tubbs and Gallaher, 2005). Seven studies, four of which were conducted with the virginia market type, favored conventional, high intensity tillage practices that could not be considered conservation tillage Grichar and Boswell, 1987;Jordan et al, 2001;Jordan et al, 2003;Minton et al, 1991;Wright and Porter, 1991a;Wright and Porter, 1995). Not surprisingly, seven other studies showed no differences in conservation tillage systems versus conventional tillage (Chapin et al, 2001;Grichar, 2006;Grichar and Smith, 1992;Grichar and Smith, 1992;Johnson et al, 2001;Wiatrak et al, 2004).…”
mentioning
confidence: 99%